2021
DOI: 10.3390/vetsci8110276
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Thoracic Ultrasonography and Airway Endoscopy in the Diagnosis of Equine Asthma and Exercise-Induced Pulmonary Hemorrhage

Abstract: Mild-moderate (MEA), severe (SEA) equine asthma and exercise-induced pulmonary hemorrhage (EIPH) are common respiratory disorders in horses. The present retrospective study aims to evaluate the role of ultrasonography and endoscopy in the diagnosis of these conditions. Three hundred and three horses were included and divided into SEA, MEA and MEA + EIPH groups, on the basis of history, clinical examination and bronchoalveolar lavage fluid (BALf) cytology; scores were assigned to lung ultrasonography, pharyngea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 57 publications
1
22
1
Order By: Relevance
“…Some authors have also reported an association between DUAO and LAI [ 9 , 28 , 30 , 31 , 32 , 33 ]; in particular, a relation between BALf neutrophilia and DDSP was reported in two studies from the same research group [ 9 , 28 ], while other studies detected an association between mild-moderate equine asthma and NPC [ 30 , 33 ]. However, multiple studies reported no association between upper and lower airways inflammation based on endoscopic and cytological findings [ 46 , 59 , 60 , 61 ], and other authors found no relationship between LAI and DUAO [ 38 ]. Similarly, in the present study, no differences between the groups were observed concerning tracheal mucus accumulation or the BALf cytological profile, suggesting that LAI is not associated with the onset of DUAO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have also reported an association between DUAO and LAI [ 9 , 28 , 30 , 31 , 32 , 33 ]; in particular, a relation between BALf neutrophilia and DDSP was reported in two studies from the same research group [ 9 , 28 ], while other studies detected an association between mild-moderate equine asthma and NPC [ 30 , 33 ]. However, multiple studies reported no association between upper and lower airways inflammation based on endoscopic and cytological findings [ 46 , 59 , 60 , 61 ], and other authors found no relationship between LAI and DUAO [ 38 ]. Similarly, in the present study, no differences between the groups were observed concerning tracheal mucus accumulation or the BALf cytological profile, suggesting that LAI is not associated with the onset of DUAO.…”
Section: Discussionmentioning
confidence: 99%
“…A 0–5 score was assigned to tracheal mucus accumulation (TM) [ 45 ]. The BALf was collected in 265 horses as follows: 60 mL of a 0.5% lidocaine hydrochloride solution was sprayed at the level of the carena to inhibit a coughing reflex, and the endoscope was passed into the bronchial tree until it was wedged firmly within a segmental bronchus; here, a 300 mL sterile saline 0.9% was instilled, and the fluid immediately aspirated [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…To perform the cytological examination, a few drops of pooled BALf were cytocentrifugated (Rotofix 32, Hettich Cyto System, Tuttlingen, Germany) at 500 rpm for 5 min. The slides were air dried, stained with May-Grünwald Giemsa and Perl’s Prussian blue, and observed under a light microscope at 400× and 1000× for 400-cell leukocyte differential counting [ 34 ]. To evaluate EIPH, 100 macrophages were assessed.…”
Section: Methodsmentioning
confidence: 99%
“…Parenchymal lesions can be localized with high accuracy but often appear very similar and cannot be differentiated via an ultrasound examination [9]. During lung inflammation, the most common occurring artifact is comet tail, which can be detected in 91% of horses with equine asthma or exercise-induced pulmonary hemorrhage [10]. However, the comet-tail artifacts are not specific as they usually suggest the presence of a small amount of fluid, without allowing to distinguish its nature (inflammatory fluid, edema, blood, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…However, the comet-tail artifacts are not specific as they usually suggest the presence of a small amount of fluid, without allowing to distinguish its nature (inflammatory fluid, edema, blood, etc.) [10]. The US complements X-ray as it is easier to use, is more sensitive in the detection of smaller amounts of fluid, and provides information about the fluid character, however, it is limited to the lung surface and has a low specificity [11].…”
Section: Introductionmentioning
confidence: 99%